Laser assisted direct energy deposition of Hastelloy-X. (January 2019) - Jinoop, A.N.; Paul, C.P.; Bindra, K.S.
Highlights: Laser assisted direct energy deposition of defect free Hastelloy-X (Hast-X). Process window is identified for defect free deposition at maximum deposition rate. Uniform deposition with fine dendritic microstructure was obtained. Potential near-net shape fabrication of complex shaped Hast-X components. Abstract: Laser additive manufacturing using direct energy deposition (LAM-DED) process uses laser beam to melt powder particles and a thin layer of substrate/previously deposited material for building near net shape of engineering components. This communication reports the process development for LAM-DED of Hastelloy-X (Hast-X) and its characterization. Process window is developed through experimental program by varying LAM-DED process parameters for defect free deposition of Hast-X at maximum deposition rate. Optical microscopy shows microstructures with fine dendrites, while the presence of FCC matrices with fine crystallites (size = 25.56 nm) are revealed during X-ray diffraction studies. Residual stress measurement reveals predominantly tensile stress on the deposited surface with a maximum value of 252 MPa. Atomic Force Microscopy revealed uniform surface topography and measured average micro-hardness is 239 HV1.96N . This research work paves a way for the fabrication of Hast-X components for various engineering applications.